Some River Draft Land Snails from Oklahoma - Leslie Hubricht (Hello World!, 1972)
These shells were collected along the South Canadian River at Whitefield, Haskell County, Oklahoma. The collection contains several species not previously reported from that State. Many of the shells had been washed from Pleistocene deposits. The numbers are the number of specimens collected, the larger numbers are estimates.